Upaya Meningkatkan Hasil Belajar Matematika Melalui Cooperative Learning Tipe TAI (Team Assisted Individualization) - Ahmad Amarullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve mathematics learning outcomes through cooperative learning type TAI (Team Assisted Individualization) in fifth grade students of SD Muhammadiyah 4 Tangerang City. This research was conducted on 30 students consisting of 14 male students and 16 female students. The learning used in this research is classroom action research using the spiral model of Kemmis and Mc Taggart. The stages of classroom action research according to Kemmis and Mc Taggart are as follows: The main concept of classroom action research consists of four components, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). The results obtained in the first cycle, students who achieved complete learning were 20 students (66.7%) with an average score of 67 student learning outcomes, the second cycle reached 25 students (83.3%) with an average learning outcome. 74 , and the third cycle reached 28 students (93.3%) with an average learning outcome of 77. In conclusion, the application of the Team Assisted Individualization learning model to fifth grade students of SD Muhammadiyah Tangerang can improve students' mathematics learning outcomes. This can be seen from the increase in class averages and students who reach the KKM. Keywords: Mathematical Ability, Team Assisted Individualization (TAI) Method